Analisis Pengendalian Piutang Usaha dan Pencatatan Utang Usaha Terhadap Peningkatan Arus Kas Pada PT Jaya Marta Sentoosa - Aisya Rahma, Siva; Sinambela, Tony R; Sugiyanta, Yohanes (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
In achieving company goals in the future, companies need to make changes, improvements, and business development. Therefore PT Jaya Marta Sentosa continues to strive to improve their business strategies to survive and not lose out in the competition. One of the improvements made by the company is in increasing the company's cash flow itself, so it is necessary to analyze financial statements to find out how to increase cash flow in the company. The analysis conducted by the author is an analysis of the control of acceptance of accounts receivable and recording of accounts payable. The purpose of this study was to determine the increase in cash flow at PT Jaya Marta Sentosa in terms of the level of accounts receivable and accounts payable to the company.The results of the analysis of this study indicate that the smooth collection of accounts receivable and payment of accounts payable can affect cash flow. This means that if the greater the collection of receivables received, the greater the cash pu; a will be received by the company, and vice versa, if the smaller the collection of receivables received, the smaller the cash will be received by the company. And for debt payments, if the greater the debt payment, the greater the cash that will be issued by the company, and vice versa, the smaller the debt payment, the smaller the cash that will be issued by the company. Therefore collection of accounts receivable and payment of debt can affect cash flow.